"Social Freedom" in the Twenty-First Century: Rereading Polanyi - Cangiani, Michele (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
Karl Polanyi's analysis of the genesis, crises, and institutional transformations of contemporary society is grounded on a theory of the basic features and dynamics of capitalism as a peculiar form of society. This article intends to develop this thesis on the basis of a reading of Polanyi's The Great Transformation, with references to Polanyi's preceding and later research. Polanyi's theoretical and methodological achievements suggest a wide comparative outlook and offer a critique of economics, in addition to being deeply connected with his political philosophy. Polanyi's approach seems to be nearer to the original institutional thought – from Karl Marx to Thorstein Veblen, from Max Weber to Adolf Löwe and Karl William Kapp – than to current neo-institutional tendencies in economics, sociology, and historiography. The hard problems society presently faces suggest the need to adhere to Polanyi's radical point of view – that is, to a radical approach to Polanyi's thought.
History; Economics
Keywords: Poor Law; WEBER; Max; 1864-1920; capitalism; comparative analysis; economic policy; economic systems; freedom in a complex society; institutional method; market society

Markets, Knowledge and Human Nature: Friedrich Hayek, Karl Polanyi and Twentieth-century Debates on Modern Social Order - Innset, Ola (European History Quarterly, 2017)
The article reads the works of Friedrich Hayek (1899-1992) and Karl Polanyi (1886-1964) in the light of their political commitments to neoliberalism and socialism respectively. It argues that both thinkers were inspired to explain history and recent events in line with these commitments in their 1944 publications, The Road to Serfdom and The Great Transformation. Furthermore, they both developed their most significant insights by attempting to counter perceived challenges from political projects to which they were opposed. Polanyi spent much of his life trying to disprove a liberal attack on socialism as out of touch with the realities of human nature, whereas it was in debates with socialists that Hayek developed a new theory of the epistemological functioning of markets, which then became foundational for the neoliberal project. Taking into account the high-stakes politics of Vienna in the interwar years is crucial for fully understanding the social theory of these two thinkers.
History
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; human behavior; knowledge; markets; neoliberalism; social order; socialist accounting; socialist calculation debate; totalitarianism

Polanyi for the Age of Trump - Krippner, Greta R. (Critical Historical Studies, 2017)
It is no exaggeration to say that Fred Block and Margaret Somers are almost singlehandedly responsible for reviving interest in Karl Polanyi’s intellectual and political legacy in American sociology. Their contribution has consisted not only in reminding sociologists of the power of Polanyi’s analysis of the rise of market society to make sense of our troubled times but even more importantly in resolving many of the difficult theoretical tangles that Polanyi gets himself into in the course of developing this analysis. Now their various essays, written over three decades, have been revised for publication in a single volume, supplemented with several new essays that introduce novel themes and also attempt to apply Polanyi’s conceptual apparatus to current social and political problems. 1 As a compilation of essays, the resulting volume defies easy summary—and I won’t attempt to offer a full treatment of the many important …
History; Sociology
Keywords: United States; capitalism; economic policy; free enterprise; historical sociology; market ideology

Karl Polanyi: A Life on the Left - Innset, Ola (European History Quarterly, 2017)
History
Keywords: DALE; Gareth; Karl Polanyi: A Life on the Left (Book); nonfiction

An Economic Prophet for Our Time - Iber, Patrick (The Chronicle of Higher Education, 2017)
Karl Polanyi knew the market couldn’t solve all ills. History is proving him correct.
History; Education
Keywords: Karl Polanyi: A Life on the Left (Book); SANDERS; Bernie; TRUMP; Donald

The moral economists: R.H. Tawney, Karl Polanyi, E. P. Thompson, and the critique of capitalism - Rogan, Tim (Princeton University Press, 2017)
A fresh look at how three important twentieth-century British thinkers viewed capitalism through a moral rather than material lens What's wrong with capitalism? Answers to that question today focus on material inequality. Led by economists and conducted in utilitarian terms, the critique of capitalism in the twenty-first century is primarily concerned with disparities in income and wealth. It was not always so. The Moral Economists reconstructs another critical tradition, developed across the twentieth century in Britain, in which material deprivation was less important than moral or spiritual desolation. Tim Rogan focuses on three of the twentieth century's most influential critics of capitalism–R.H. Tawney, Karl Polanyi, and E.P. Thompson. Making arguments about the relationships between economics and ethics in modernity, their works commanded wide readerships, shaped research agendas, and influenced public opinion. Rejecting the social philosophy of laissez-faire but fearing authoritarianism, these writers sought out forms of social solidarity closer than individualism admitted but freer than collectivism allowed. They discovered such solidarities while teaching economics, history, and literature to workers in the north of England and elsewhere. They wrote histories of capitalism to make these solidarities articulate. They used makeshift languages of "tradition" and "custom" to describe them until Thompson patented the idea of the "moral economy."
History; Political Science
Keywords: HENRY; Richard; PALMER; Edward; TAWNEY; R.H.; THOMPSON; E.P.; capitalism; moral and ethical aspects; moral economy; socialism